Electric discharge in the transverse air flow at atmospheric pressure - Prysiazhnevych, I.V.; Martysh, Eu.V.; Lisitchenko, T.E. (Вопросы атомной науки и техники, 2012)
Physical features of the transverse arc discharge and its atmospheric pressure plasma were investigated for the different gas flow rates (gas flow velocity ~ 0…2/3 of the sound speed) and character of the gas flow (laminar/turbulent). Component composition of the plasmaforming gas; electronic excitation temperatures Te* of atoms, vibrational Tv * and rotational Tr* temperatures of molecules in the generated plasma were determined by optical emission spectroscopy. Founded difference of the temperatures Tе*(Cu)>Tе*(O, H) was explained by the additional mechanism of the population of the excited electronic states of cooper atoms (material of electrodes) due to the ion-ion recombination, which is almost absent for the blowing gas atoms. Non-monotonic character of the Tr*(N₂) and Tr*(N₂₊) dependence on the gas flow was connected with transition from laminar to the turbulent gas flow regime. It was shown that at large gas flows (at which the deviation from laminar flow occurs and the turbulence starts) plasma of TA becomes more isothermal.